Sintomas depressivos e desesperança em pessoas em situação de rua atendidas em instituições de apoio em uma capital brasileira - Lopes, Joyce Vânia Rodrigues (2019)
The investigation of the mental health in homeless, expands the construction of the knowledge and can contribute, in a significant way, to an effective attention to the health of these individuals. This study aimed to investigate the hopelessness and depressive symptomatology, moderate to severe, in the street population of a Brazilian capital of Central Brazil. A crosssectional, analytical study carried out between July and August of 2017 in two municipal public units that provide specialized services to this population. The depressive symptomatology was investigated through the Beck Depression Inventory (BDI) and hopelessness through the Beck Despair Scale (BHS). Bivariate and multiple analyzes were performed. Variables with p-value less than 0.20 in bivariate analysis and age, as potential confounders, were included in a multivariate Poisson model with robust variance. Spearman correlation analysis was used to verify the relationship between BDI and BHS. A total of 132 people participated in the study, with a mean age of 37.4 years. The majority of the participants were single (57.6%), black (82.6), heterosexual (94.7%), natural of the central-west region, male (78.8%) 12 months or less (70.5%) and with a low level of education, with less than 8 years of formal education (56.8%) predominating. Substance use was manifested by the majority (92.4%). Suicidal ideation (40.9%) and psychological / psychiatric treatment (47%) were present at a significant level. Among the individuals in the street situation investigated, 24.2% (95% CI: 17.7 - 32.2) and 49.2% (95% CI: 30.9-57.7) reported hopelessness and moderate to severe depressive symptomatology, respectively. Moderate to severe depressive symptomatology prevailed in women (PR: 1.42, p = 0.048) and in those with homosexual or bisexual orientation (PR: 1.81; p = 0.001). Homosexual or bisexual sexual orientation and religion were statistically associated with moderate to severe symptomatology. Practicing some religion was considered a protective factor, and decreased by 32% the chance of presenting moderate to severe depressive symptomatology (RPaj: 0.68; 95% CI: 0.47-0.99). On the other hand, homosexual or bisexual orientation increased the probability of presenting moderate to severe depressive symptomatology by 89% (RPaj: 1.89, 95% CI: 1.18-3.04). Moderate to severe despair prevailed in women (PR: 2.54, p = 0.001), in individuals with suicidal ideation (RP: 1.86, p = 0.048), and was lower in those who used alcohol (RP: 0, 49; p-value: 0.019) or tobacco (RP: 0.47, p = 0.018). Sex, schooling, tobacco use and crack use were statistically associated with moderate to severe hopelessness. Being female increased 132% (RPaj: 2.32, 95% CI: 1.24- 4.99) the chance of the individual presenting moderate to severe hopelessness. Being a tobacco user decreased by 52% (RPaj: 0.48, 95% CI: 0.27-0.87) and being a crack or similar user increased by 154% (RPaj: 2.54, 95% CI: 1.25 -5.17) when compared to non-users of this substance. Those with education of 8 to 11 years of study (RPaj: 2.72, 95% CI: 1.20- 6.14) and greater than 12 years of study (RPaj: 2.62, 95% CI: 1.31 -5.25) were more prevalent when compared to individuals with lower education (less than 8 years of schooling). Furthermore, a moderate positive correlation was observed between the two scales (r = 0.525, p <0.001). The high rates of moderate to severe depressive symptomatology and the considerable index of moderate to severe hopelessness point to the need for greater attention to the mental aspect of the street population. More accentuated indexes in women indicate that this is a portion that demands care specific to their particularities.